LAND SNAILS - Mohd Zacaery, Khalik; Mohammad Effendi, Marzuki (UNIMAS Publisher and Natural History Publications (Borneo) Sdn. Bhd., 2023)
Gastropods show high diversifi cation of shell shapes and sculptures. In the tropics, gastropods could be encountered in a variety of habitats. Taxonomically, gastropods are classifi ed in the phylum Mollusca, and have been estimated to contribute approximately 80% of the total species richness. In general, terrestrial gastropods come in three forms: (1) shelled snails, the constructed shell is used to accommodate the soft body; (2) reduced shell, known as semi-slugs, with visible external shell but not large enough for the soft body to fi t in, or with internal minute shell which is not visible to the naked eye, and (3) true slugs, or those that have no shells.